2020
DOI: 10.1515/nanoph-2019-0489
|View full text |Cite
|
Sign up to set email alerts
|

Observation of an exceptional point in a non-Hermitian metasurface

Abstract: AbstractExceptional points (EPs), also known as non-Hermitian degeneracies, have been observed in parity-time symmetric metasurfaces as parity-time symmetry breaking points. However, the parity-time symmetry condition puts constraints on the metasurface parameter space, excluding the full examination of unique properties that stem from an EP. Here, we thus design a general non-Hermitian metasurface with a unit cell containing two orthogonally oriented split-ring resonators (SRR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 28 publications
0
38
0
Order By: Relevance
“…1A in the main text). The structure can be modeled using coupled-mode theory inspired from the references of (19)(20). The effective dipole moment of the structure is 𝑝 𝑥,𝑦 = 𝑝 ̃𝑥,𝑦 𝑒 𝑖𝜔𝑡 , which couples strongly to an incident radiation field 𝐸 𝑖 = 𝐸 ̃𝑖𝑒 𝑖𝜔𝑡 with a radiative coupling strength 𝑔 𝑗 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A in the main text). The structure can be modeled using coupled-mode theory inspired from the references of (19)(20). The effective dipole moment of the structure is 𝑝 𝑥,𝑦 = 𝑝 ̃𝑥,𝑦 𝑒 𝑖𝜔𝑡 , which couples strongly to an incident radiation field 𝐸 𝑖 = 𝐸 ̃𝑖𝑒 𝑖𝜔𝑡 with a radiative coupling strength 𝑔 𝑗 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous works on metasurfaces have shown that non-Hermitian metasurfaces can operate close to an EP, and have approached the singularity thanks to a series of individually-distinct metasurfaces for which a given parameter is changed (16)(17)(18)(19). The exploitation of the robust topological phase around the EP, referred to as exceptional topological (ET) phase, to realize functional devices has remained elusive.…”
mentioning
confidence: 99%
“…When the EP is reached, the two eigenpolarization states merge into a circularly polarized state despite the lack of rotational symmetry of the non-Hermitian metasurface. Park et al also designed a non-Hermitian metasurface with a similar architecture to explore the topology of EP encirclement in the parameter space of coupling strength and incident wavelength [65]. The topology of the self-intersecting Riemann surface that is unique to non-Hermitian systems [9,66,67] has been observed by the behavior of level crossing in the magnitude and phase of the eigenvalues.…”
Section: Polarization Controlmentioning
confidence: 99%
“…To uncover the dynamics of EP encirclement in polarization space, a series of metasurface samples with different geometric parameters need to be fabricated to control the coupling strength near the EP [34,71], which make it difficult to fine-tune parameters and may induce undesired perturbations due to fabrication errors. To solve this problem, the wavelength and angle of incident light have been selected as the parameter space to continuously control the phase transition around EP and observe its topological structure [65,71]. Reconfigurable metasurfaces have also been proposed to analyze the evolution of EP in polarization space to avoid the requirement of a great number of experimental samples.…”
Section: Polarization Controlmentioning
confidence: 99%
“…Here, the paradigm shift comes from the idea of primarily manipulating the imaginary part of the refractive index of the resonator or its surrounding environment by introducing losses and/or gain into the system. Following this approach, experimental observation of the transition through exceptional point (EP) [11][12][13] has been reported, followed by theoretical and modeling results predicting the ability to design optical devices for the control of light at the nanometer scale [14][15][16] and to obtain spectral singularities in active hybrid metamaterials [17][18][19][20]. The exceptional point is not the whole story, however.…”
Section: Introductionmentioning
confidence: 99%